Variation of the chemical composition of street dust in a highly industrialized city in the interval of ten years - Švédová, Barbora; Matýsek, Dalibor; Raclavská, Helena; Kucbel, Marek; Kantor, Pavel; Šafář, Michal; Raclavský, Konstantin (Journal of environmental management, 2020)
Street dust can be re-suspended into the atmosphere by wind and vehicle passage in an urban area. Street dust is affecting the environmental quality of the atmosphere and human health. A detailed study was conducted to determine the changes in concentrations of heavy metals and magnetic susceptibility by comparison of samples of street dust obtained in the years 2008 and 2018 at the same localities. An amount of dust per m2 of road area was highly variable for individual localities (47 g/m2 - 1.37 kg/m2), with arithmetic mean (229.7 ± 85.97 g/m2) in the year 2018. Silt particles in street dust (<0.063 mm) represented approx. 15-20%, sand particles approx. 63-70% and gravel 10-20%. Iron (5-6%) has significant concentrations in street dust. The highest concentrations are represented by the series Mn ˃ Zn ˃ Cr ˃ Cu ˃ Pb ˃ Ni. Comparison of metal concentrations in the years 2008 and 2018 showed a comparable level of iron and a lower level of lead. The significant enrichment was found for Cu, Cr and Zn expressed by enrichment factor in the range from 5 to 20. High values of magnetic susceptibility of street dust are caused by metallurgy. Metals except Cu are bound in magnetic particles and have a high correlation coefficient with magnetic susceptibility.
Keywords: Metallurgical industry; China; velkoměsta; Environmental Monitoring; hodnocení rizik; Heavy metals; Risk Assessment; Dust; monitorování životního prostředí; těžké kovy; X-ray fluorescence; Street dust; lidé; Cities; prach; Humans; Magnetic susceptibility; Čína; Metals, Heavy